2021
DOI: 10.1038/s41443-021-00480-1
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic labiaplasty on minors: a review of current trends and evidence

Abstract: Cosmetic labiaplasty is a form of Female Genital Cosmetic Surgery (FGCS) that is performed with the deliberate intent to alter the appearance and morphology of the external genitalia in the absence of medical concerns. Over the last decade, there is an increasing demand for FGCS and the industry behind it is constantly growing. Adolescents comprise an extremely vulnerable population, with labiaplasties in this particular age group having also increased. However, labiaplasty has been widely contested due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…intersex genital cutting, or routine penile circumcision in the Global North, although these, too, can be substantial) (Beh and Diamond, 2000;Creighton, 2001;Diamond and Garland, 2014;Darby, 2015;Fahmy, 2019;Learner et al, 2020;Gress, 2021;Kalampalikis and Michala, 2021;Schröder et al, 2021). To illustrate, health department records from the Eastern Cape region of South Africa show that more than five thousand Xhosa boys required hospitalization due to their traditional circumcisions between 2006 and 2013; there were 453 recorded deaths among initiates within this time period and 214 circumcision-related penile amputations (Meissner and Buso, 2007;Meel, 2010;Douglas and Nyembezi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…intersex genital cutting, or routine penile circumcision in the Global North, although these, too, can be substantial) (Beh and Diamond, 2000;Creighton, 2001;Diamond and Garland, 2014;Darby, 2015;Fahmy, 2019;Learner et al, 2020;Gress, 2021;Kalampalikis and Michala, 2021;Schröder et al, 2021). To illustrate, health department records from the Eastern Cape region of South Africa show that more than five thousand Xhosa boys required hospitalization due to their traditional circumcisions between 2006 and 2013; there were 453 recorded deaths among initiates within this time period and 214 circumcision-related penile amputations (Meissner and Buso, 2007;Meel, 2010;Douglas and Nyembezi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, diagnosis coding may limit our analysis if alternative diagnoses were provided, and the population with the highest utilization is likely not eligible for Medicare or Medicaid given age and income. Nevertheless, given the limited outcome data and potential long-term adverse events associated with this procedure, including scarring, infection, chronic sexual dysfunction, wound breakdown, and regret, 3,4,6 as well as the high rate of minors undergoing this procedure, more dedicated research assessing the prevalence and associated outcomes is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide Ambulatory Surgery Sample data do not allow us to determine whether procedures were considered medically indicated or cosmetic or the degree of patient bother, though it is notable that most cases of symptomatic labial hypertrophy can be treated with supportive measures and do not require surgical correction. 4–6…”
Section: Discussionmentioning
confidence: 99%
“…A study of Australian general practitioners (GPs) in 2016 found that over a third of GPs surveyed had consulted with patients aged under 18 years for FGCS 9 . International evidence also suggests that young women and girls seek these procedures 10 . A 2021 study reported a high complication rate (20.5%) of labioplasty in an adolescent population ( n = 17), with a 6.8% reoperation rate.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…Regarding adolescents and FGCS, the Society of Obstetricians and Gynaecologists of Canada further contends that ‘such procedures [FGCS] should not be offered until complete maturity including genital maturity, and parental consent is not required at that time’ 22 and advise that physicians who consult adolescent patients requesting FGCS require additional expertise in adolescent health. A 2021 review of cosmetic labioplasty on minors recommends that adolescent patients with genital appearance concerns should: (i) be counselled in the first instance about the wide range of ‘normal’ genital appearance to ameliorate any body image concerns; (ii) be referred to an experienced mental health professional if mental health issues are identified; and (iii) delay labioplasty until adulthood to ensure a well‐informed decision about FGCS can be reached 10 …”
Section: What Is Already Known On This Topicmentioning
confidence: 99%